The impact of quality management systems on improving logistics customer service in distribution processes - Dominik Zimon (International Journal of Supply Chain Management, 2017)
The main objective of the publication is to determine to what extent the implementation of the requirements of standardized quality management system supports the logistics customer service in the process of distribution. The research process was carried out in January 2017 in 21 organizations that have implemented and certified ISO 9001 quality management system for at least 5 years. The research organizations belong to medium-sized enterprises and operate in Poland. Based on the analysis of the results of the research, it can be concluded that the implementation of the requirements of the ISO 9001 standard has a significant positive influence on the improvement of logistic customer service. That confirms the indication of 76% of respondents.